2021
DOI: 10.1007/978-3-030-68869-1_1
|View full text |Cite
|
Sign up to set email alerts
|

Solving Multivariate Polynomial Systems and an Invariant from Commutative Algebra

Abstract: The complexity of computing the solutions of a system of multivariate polynomial equations by means of Gröbner bases computations is upper bounded by a function of the solving degree. In this paper, we discuss how to rigorously estimate the solving degree of a system, focusing on systems arising within public-key cryptography. In particular, we show that it is upper bounded by, and often equal to, the Castelnuovo-Mumford regularity of the ideal generated by the homogenization of the equations of the system, or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…In § 2.1, we briefly recall the definitions of solving degree and degree of regularity. We limit ourselves to the basic notions necessary to define these two invariants and we refer to [CG21] for a more detailed exposition. In § 2.2, we recall the construction of Weil restriction and we present an algebraic proof of Weil's Theorem in the affine case.…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations
“…In § 2.1, we briefly recall the definitions of solving degree and degree of regularity. We limit ourselves to the basic notions necessary to define these two invariants and we refer to [CG21] for a more detailed exposition. In § 2.2, we recall the construction of Weil restriction and we present an algebraic proof of Weil's Theorem in the affine case.…”
Section: Preliminariesmentioning
confidence: 99%
“…Notice that the solving degree is still an upper bound on the degree in which the algorithms adopting this variation terminate. See also [CG21,Remark 6] for a more detailed discussion.…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…This motivated the introduction of several algebraic invariants related to the solving degree. The main ones are the first [9,8] and last fall degrees [15], the degree of regularity [2,1], and the Castelnuovo-Mumford regularity [4]. These invariants are routinely used within the cryptographic community in order to estimate the solving degree.…”
Section: Introductionmentioning
confidence: 99%
“…Several connections between these invariants, both heuristic and proven, are known. In [4] we have shown that, under suitable assumptions, the Castelnuovo-Mumford regularity of the homogenization of a system is an upper bound for its solving degree. In [14] the authors outlined an algorithm to compute the solution of a polynomial system and provided an upper bound on its complexity in terms of its last fall degree.…”
Section: Introductionmentioning
confidence: 99%